2022
DOI: 10.1186/s12909-022-03229-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing medical and nursing students’ willingness to care for COVID-19 patients in South Korea: a cross-sectional study

Abstract: Background The COVID-19 pandemic has threatened the stability and adequacy of the global healthcare system. In this situation, authorities have considered engaging medical and nursing students to address the shortage of frontline healthcare workers. This study investigated the effect of COVID-19-related knowledge, attitudes, and preventive behaviors on medical and nursing students’ willingness to care for COVID-19 patients. Methods Medical and nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Several studies about disaster medicine preparedness and readiness among health care profession students. 7,[19][20][21] A study in Pakistan among healthcare profession students found that students' levels of readiness to practice were moderate. 19 Kang et al 22 realized that additional mental health services and training should be available to at-risk medical rescuers and groups to ensure that they are adequately prepared for relief efforts and to maintain their mental health after assistance in disaster relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies about disaster medicine preparedness and readiness among health care profession students. 7,[19][20][21] A study in Pakistan among healthcare profession students found that students' levels of readiness to practice were moderate. 19 Kang et al 22 realized that additional mental health services and training should be available to at-risk medical rescuers and groups to ensure that they are adequately prepared for relief efforts and to maintain their mental health after assistance in disaster relief.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of training models have been developed. [21][22][23] According to the participants, pharmacy students deployed in disaster areas, could be expected to have more opportunities to be involved in various organizations activities. Student membership within professional organizations are key components to advancing the profession of pharmacy.…”
mentioning
confidence: 99%
“…Zhong et al (2022) found that attitude predicts less but significantly the intentions of student nurses to voluntarily care for COVID-19 patients. Kim et al (2022) found that the optimistic attitude of medical and nursing students positively affects their intention to take care of COVID-19 patients. Hence, students' attitudes can predict behavioral intention to volunteer.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Knowledge of SPs is introduced as a part of the undergraduate course curriculum in pre-final professional year (third year of the Indian medical education curriculum) of the MBBS and in the first and second years, respectively, of the graduate nonmatriculated nursing and bachelor of nursing courses [ 21 , 22 ]. However, the failure to gain knowledge and exercise SPs during undergraduate years might lead to the poor practice of SPs in the future, leading to increased HAI rates [ 21 , 22 ]. Moreover, the gap in knowledge and practice is another issue to investigate.…”
Section: Introductionmentioning
confidence: 99%